ECOLOGIES OF HUNGER IN DALIT LIVES: A BRONFENBRENNERIAN STUDY OF THE PRISON WE BROKE - Gothwal, Pooja; Malik, Sonia (International Journal of Research -GRANTHAALAYAH, 2025)
The study examines the multifaceted nature of hunger in Dalit lives as portrayed in Baby Kamble’s The Prison We Broke. Utilizing Urie Bronfenbrenner’s Socio-Ecological Model, the research maps how hunger is reproduced and experienced across interconnected ecological layers. While hunger is commonly understood as physical deprivation, this study foregrounds its broader social, emotional, and identity-based dimensions, revealing the ways in which hunger shapes and is shaped by experiences at the individual, familial, communal, and structural levels. The paper addresses a significant gap in the scholarship, where the ecology of hunger, particularly within Dalit autobiographical narratives, remains underexplored. Through qualitative textual analysis framed by ecological theory, the research shows how individual bodily starvation is embedded within family survival practices, sustained by communal networks, and perpetuated by macro-level caste discrimination and state neglect. These factors systematically sustain hunger and marginalization of Dalit communities. Importantly, the study also highlights forms of Dalit resistance that transcend mere physical nourishment. It emphasizes the struggle for dignity, selfhood, and collective identity, portraying hunger as not only a material condition but also a contested space where Dalits affirm their humanity and fight structural inequalities. The findings contribute to a nuanced, dynamic understanding of hunger as a layered phenomenon deeply entwined with caste-based oppression by revealing how hunger itself functions as a form of structural violence.